Marketing and Personal Branding of Anies Baswedan as Presidential Candidate by NasDem Party in Digital Space - Muhammad Hazim Khabir; Suswanta Suswanta; Ridho Al-hamdi (Ikatan Sarjana Komunikasi Indonesia, 2024)
The purpose of this study is to see the phenomenon of political marketing, especially how the online mass media builds Anies Baswedanâ€™s branding as a presidential candidate. The branding of presidential candidate serves as a phenomenon of Indonesian national politics particularly when NasDem Party declared Anies Baswedan as a presidential candidate on October 3, 2022. The methodology of this study uses qualifiers, and the technique of analysis and data analysis uses Nvivo12 plus mainly in online media reporting in Indonesia (CNN, Kompas, Media Indonesia, and Detik.com). Â The results of this study showed that the four media outlets were actively reporting on the nomination of Anies as a presidential candidate. The massive reporting put Anies' personal electability ahead of other political opponents. The identification is based on the analysis of content about Anies in the four online media outlets. In terms of quantity, Media Indonesia more actively reported on Anesâ€™ candidacy than the other three media outlets. This is because of power polarization relationship in terms of ownership relationship between NasDem Party and Media Indonesia. Thus, the news frame leans towards Anies and indirectly it can be used for marketing and branding politics.